Processos de formação do acervo da biblioteca da Academia Imperial de Belas Artes e seu uso como material didático - Godoy, Rosani (2015)
This research aims to demonstrate the processes of formation of “Biblioteca da Academia Imperial de Belas Artes (AIBA)”. We will analyze its historic aspects with the purpose of rebuilding the process of formation of a collection which keeps in itself the institutional memory of the artistic education in Brazil. We will analyze the way the acquisitions were made and the actions taken, aiming to characterize what today we would call “policies for collection acquisition”, by the directors of AIBA. In this aspect, two characters stand out: Felix Emilio Taunay (1795-1881), director of “Academia” from 1834 to 1851 and Manuel de Araujo Porto-alegre (1806-1879), director of “Academia” from 1854 to 1857. Our objective is to analyze the constitution of this collection focusing on the formation of the artists in the 19th century. The solid bases practiced by Taunay in the method of teaching lasted great part of the 19th century. It was also in this moment that the basis of the collection for the “Biblioteca” was constructed, giving directions to future actions of other directors that came to direct the “Academia” and the “Biblioteca”. The management of Porto-alegre, from 1854 to 1857, and “Reforma Pedreira” set up by him were a landmark in the education of AIBA, with the inclusion of new chairs, even influencing the evaluations for the acquisitions of new work that would become part of the collection of the “Biblioteca”. In this context we will characterize the processes of formation of the collection of the “Biblioteca da Academia Imperial de Belas Artes (AIBA)” in the light of the literature and of primary documents available in records and libraries, among which, the historic records of “Museu D. João VI” standing out the contribution of the collection of “Biblioteca” of AIBA to the teaching of “Belas Artes”, developed in the old “Academia Imperial de Belas Artes” in the 19th century. We concluded that the collection made it possible to enable the education of art in Brazil. The “Biblioteca da AIBA” spread culture and also served as a space for sociability. The “policy for the collection acquisition” was well succeeded for having AIBA invested in the acquisition and encouraged the donation of works of art of interest to the formation of artists, also for having the directors and secretaries as selectors, mainly Taunay and Portoalegre that were highlighted in all the process of formation of “Biblioteca”, guiding future directors of AIBA that continued the work of selection and acquisition. The Professors Comissions provided a positive effect, since the appointed professors were experts in the area. The analysis of primary documents produced in the 19th century allowed the identification of this innovative experience to the time, whose knowledge isn’t available in other sources of study. The teaching model used by “Academia”, with the support of an updated and capable “Biblioteca”, even for the European standards of that time, brought so efficient results, that modified a whole generation of artists. The “Biblioteca da Academia” was privileged to have been made at the time of the nation building. It was a generation committed to the independence, so they brought the European culture to Brazil through books, enabling that the “Academia” became efficient making artists and representing Brazil through the art. The data obtained in the research will be used as instrument of management and safeguard to the rare and special collection of “Biblioteca de Obras Raras da Escola de Belas Artes” of UFRJ.